A STUDY OF RELATIONSHIP OF COGNITIVE STYLES WITH STUDENTS’ ACADEMIC ACHIEVEMENT IN THE SUBJECT OF SCIENCE AT ELEMENTARY LEVE - Shagufta Akhtar, Manzoor Arif, (PJE, 2023)
This paper aimed at investigating the relationship of cognitive styles with students’ academic achievement in the subject of science at elementary level. A sample of 511 students, studying in 8th class, was taken from five Pakistani public sector secondary schools. The data collected through the study instruments were analyzed by using Pearson product moment correlation, partial correlation and test. Results indicate that male students tended to be more field dependent, while female students were more inclined towards field independence and the low achievers were found to be field dependent while high achievers tended to be field independent.